Análise qualitativa do desempenho da gestão no Sistema de Excelência do Exército Brasileiro (SE-EB) e seus impactos nos projetos estratégicos dos arsenais de guerra - Oliveira, Priscila de Andrade (2018)
The Federal Public Administration, through the Brazilian Army, has developed sever- al defense projects, aiming to fulfill its institutional mission and seeking the develop- ment of quality in its projects. The Brazilian Army, through its Management Excel- lence Model, has sought, over the years, to improve the management of its strategic projects with the implementation of a management system and the use of managerial tools recommended by institutions of international recognition. Following this theme, the present study had as general objective to evaluate the performance of the man- agement in the System of Excellence of the Brazilian Army in the War Arsenals, through the analysis of the Management Plans and their performance indicators. For this, the methodology defined as the most adequate and used in the accomplishment of the research was of a qualitative nature, of the descriptive type. After designing the research, the units involved in the theme were: War Arsenals and the Manufacturing Board. For the data collection, interviews were carried out with the advisors and for- mer management advisors of the System of Excellence of the Manufacturing Direc- torate, of the Rio Arsenal War Arsenal, of the War Arsenal of São Paulo and of the General Chamber War Arsenal. Bibliographical and documentary research was also carried out on military organizations that participated in quality management awards. The results indicated the degree of development of the management of the War Ar- senals and their current impacts on the planned management goals. One of the con- clusions of this study was to verify that the Management Excellence System, when executed in the way that is guided by the Program, is beneficial since its first man- agement cycle, and with its continuous development, the institution that implements it, has progressive gains in governance of its management. Another conclusion was to identify that Arsenals, despite having implemented the System of Management Excellence, did not evolve in their management, demonstrating a lack of maturity in the elaboration of their Management Plans.